EFL Students’ Performance and Expectation Towards Peer Response in Writing Classroom - M. Zaini Miftah (IJEE (Indonesian Journal of English Education), 2016)
ABSTRACT This study investigates the EFL students’ performance and expectation towards peer response in writing classroom. A survey research method was applied. Data were collected through a questionnaire containing 20 items. The questionnaire was distributed to 12 Indonesian EFL students enrolling in a writing course at the English Department of IAIN (State Islamic Institute) Palangka Raya, Central Kalimantan, Indonesia. The findings of the study showed that the tendencies of the tasks performed by the student reviewers are asking about peers’ ideas and meanings of their essays, of the student-writers responses to peer response are paying attention to clear correction and correcting mechanical errors, and of the student-writers expectations from the peer response are commenting on ideas and meanings, providing clear corrections, and correcting mechanical errors. ABSTRAK Penelitian ini mengkaji performa dan harapan mahasiswa dalam konteks EFL terhadap respon teman sejawatnya dalam kelas menulis. Metode penelitian survey diterapkan dalam penelitian ini. Data dikumpulkan menggunakan kuesioner dengan 20 pertanyaan. Kuesioner ini diberikan kepada 12 mahasiswa EFL di Indonesia pada kelas menulis Prodi Pendidikan Bahasa Inggris IAIN (Institut Agama Islam Negeri) Palangka Raya, Kalimantan Tengah, Indonesia. Sebagai hasil dari penelitian, terlihat bahwa kecenderungan tugas yang dilakukan oleh mahasiswa sebagai penyunting adalah bertanya tentang ide-ide dan makna dari esai teman sejawatnya, kecenderungan tanggapan dari mahasiswa sebagai penulis terhadap respon teman sejawat adalah memperhatikan koreksi yang jelas dan mengoreksi kesalahan mekanik, dan kecenderungan harapan mahasiswa sebagai penulis terhadap respon teman sejawat yaitu mengomentari ide dan makna, memberikan koreksi yang jelas, dan juga mengoreksi kesalahan mekanik dari esai teman sejawatnya. How to Cite: Miftah, M., Z. (2016). EFL Students’ Performance and Expectation Towards Peer Response in Writing Classroom. IJEE (Indonesian Journal of English Education), 3(2), 208-223 doi:10.15408/ijee.v3i2.5513. Permalink/DOI: http://dx.doi.org/10.15408/ijee.v3i2.5513